Nasopharyngeal Burkitt lymphoma masquerading as adenoid hypertrophy in an adult: a diagnostic challenge - D., Deepika Eswari; Pai, Sunil; Kumar, Ajay; Shenoy, Ramnath; Rosario, David; Nischal, Hanock; J., Herison (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
This case report presents the diagnostic challenges encountered in identifying nasopharyngeal Burkitt lymphoma (BL) in an 18- year-old male initially misdiagnosed with adenoid hypertrophy. BL, a rare and aggressive B-cell non-Hodgkin’s lymphoma (NHL), typically manifests in cervical lymphnodes or facial bones, making nasopharyngeal involvement unusual. The patient's symptoms progressed from nasal blockage to oropharyngeal dysphagia and neck swelling, prompting further investigation. Radiological assessments, including a CT scan, were inconclusive, leading to a diagnosis through excisional biopsy and immunohistochemistry, confirming BL with CD20, CD10, and Bcl-6 expression. Successful treatment involved six cycles of chemotherapy, resulting in complete remission. This case underscores the importance of considering rare malignancies in atypical presentations and highlights the role of comprehensive diagnostic approaches in achieving accurate and timely management.